The agglomeration wage differential reconsidered - an investigation with German micro data 1984-1997 - Joachim Möller; Anette Haas (European Regional Science Association (ERSA), 2002)
The paper analyzes the agglomeration wage differerential using panel micro data with regional information for the time period 1984-1997. Referring to new contributions to regional economics, several theoretical explanations for spatial wage differentials are discussed. The empirical approach differentiates between two sectors of the economy (Manufacturing and Services), three skill groups and the position in the wage hierarchy. After presenting some descriptive evidence we use Chamberlain's (1996) method of quantile regressons for the estimatons. According to our findings an agglomeration differential does exist except for low-skilled service workers. The agglomeration wage differential depends positively on the skill level, is typically higher in the manufacturing than in the service sector and tends to increase with the decile of the wage distribution. Our results indicate that a doubling of employment density leads to gross wage increase of 2.5 percent in the average.
Keywords: 330